Recent Progress on the Development of Porous Bioactive Calcium Phosphate for Biomedical Applications - Abdurrahim, Toibah; Sopyan, Iis (Recent Patents on Biomedical Engineering (Discontinued), 2008)
Hydroxyapatite (HA) and tricalcium phosphate are two members of the calcium phosphate compounds which have been used clinically for many years. Their good biocompatibility is attributed by its similar chemical composition to that of bone material. Porous calcium phosphate ceramics have found enormous use in biomedical applications including bone tissue regeneration, cell proliferation, and drug delivery. In bone tissue engineering it has been applied as filling material for bone defects and augmentation, artificial bone graft material, and prosthesis revision surgery. Their high surface area leads to excellent osteoconductivity and resorbability providing fast bone ingrowth. Many efforts on the development of porous calcium phosphates can be observed from a considerable numbers of patents which have been filled recently on various methods for preparing porous calcium phosphate for applications of bone implant, chromatography and so on. Porous calcium phosphate can be produced by a variety of methods including conversion of natural bones, ceramic foaming technique, polymeric sponge method, gel casting of foams, solvent casting/ salt leaching method, selective laser sintering, precision extrusion deposition, starch consolidation, microwave processing, slip casting, and electrophoretic deposition technique. Some of these methods have been combined to fabricate porous calcium phosphate with improved properties. These combination methods have yielded some promising results. This paper discusses briefly the fundamental aspects of porous calcium phosphate for biomedical applications as well as the various techniques used to prepare porous calcium phosphate.
Keywords: bioactive